1994
DOI: 10.1093/infdis/170.1.140
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Polymorphonuclear Leukocytes with Yersinia enterocolitica: Role of the Yersinia Virulence Plasmid and Modulation by the Iron-Chelator Desferrioxamine B

Abstract: The impact of desferrioxamine B (DFOB) on intracellular calcium mobilization, chemoluminescence (CL) signaling, phagocytosis, and bacterial killing of Yersinia enterocolitica by polymorphonuclear leukocytes (PMNL) was investigated. DFOB did not alter calcium signaling in PMNL but transiently increased phagocytosis. Likewise, higher counts of viable bacteria in PMNL and increased CL signals after stimulation with Y. enterocolitica were observed in the presence of DFOB. However, DFOB reduced the CL signal elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 53 publications
5
34
0
Order By: Relevance
“…DFO inhibits proliferation of T and B lymphocytes and cytokine production of macrophages and modulates interaction of polymorphonuclear leukocytes with yersiniae (3,21). In keeping with these observations, we and others have demonstrated that DFO increases pathogenicity of Y. enterocolitica in mice, resulting in fatal septicemia and shock (5,39,40).…”
supporting
confidence: 81%
“…DFO inhibits proliferation of T and B lymphocytes and cytokine production of macrophages and modulates interaction of polymorphonuclear leukocytes with yersiniae (3,21). In keeping with these observations, we and others have demonstrated that DFO increases pathogenicity of Y. enterocolitica in mice, resulting in fatal septicemia and shock (5,39,40).…”
supporting
confidence: 81%
“…The presence of HPI in bacteria using different pathogenic strategies supports the theory that it is not involved in pathogenesis but in increasing fitness by iron acquisition, which is essential for bacteria. Since most HPI-positive bacteria carry additional iron acquisition systems, such as enterochelin in E. coli, with higher affinity to iron, other functions of HPI such as modulation of the cellular host defense by yersiniabactin have been discussed (88,285).…”
Section: Enterohemorrhagic E Colimentioning
confidence: 99%
“…route) were recovered. A piece of each organ was prepared for cryosectioning as previously described (13). Briefly, tissues were embedded in Tissue-Tek O.C.T.…”
Section: Methodsmentioning
confidence: 99%